Blockchain Applications in Education Affecting Challenges and Problems in Digital - Warry Saputra, Multama Agung; Ochtaffia, Dinnda; Apriani, Desy; Yusfi, Sheilla Chareza; Gori, Murnitati (Blockchain Frontier Technology, 2023)
Blockchain is thought to have a significant potential to offer a wide range of benefits for education development because of its special properties of decentralization and security. Its use in schooling is quite new. new but expanding swiftly. This paper described the standard blockchain. Briefly describe procedures and qualities. then, current blockchain applications thorough summaries of the findings in education, especially those Learning record keeper, decentralized education ecosystem, and credential issuance and management. The final topic of discussion was obstacles, both technical and otherwise. It is intended to give a thorough examination of the potential applications of blockchain. aid in the creation of new application systems and assist in the evolution of education.